Analysis of Financial Compensation and Work Flexibility on Employee Loyalty Through Employee Job Satisfaction in West Java Gas-Fire Power Plant - Adiatmaputra, Anindyo Pradipto; Nur, Dhani Ichsanuddin; Purwanto, Sugeng (PT. Maju Malaqbi Makkarana, 2025)
This study aims to analyze the influence of financial compensation and work flexibility on employee loyalty, and to examine the role of job satisfaction as a mediating variable. This study focused on employees of the West Java Gas and Steam Power Plant (PLTGU) to understand how these factors influence their level of loyalty to the company.This study used a quantitative approach using a census method, sampling the entire population, consisting of 49 employees of the West Java PLTGU Operations Division. The data analysis technique used was Partial Least Squares (PLS) to test the direct and indirect relationships between variables in the research model. The results showed that financial compensation had a positive and significant effect on employee loyalty. Work flexibility was also shown to have a positive effect on loyalty, although this effect was not mediated by job satisfaction. Meanwhile, job satisfaction acted as a significant mediator in the relationship between financial compensation and employee loyalty. These findings suggest that employee loyalty can be enhanced through both increased compensation and direct provision of work flexibility.